Chitosan-Based Hydrogels for Bioelectronic Sensing: Recent Advances and Applications in Biomedicine and Food Safety - Si Wu; Shijing Wu; Xinyue Zhang; Tao Feng; Long Wu (Biosensors, 2023)
Due to the lack of efficient bioelectronic interfaces, the communication between biology and electronics has become a great challenge, especially in constructing bioelectronic sensing. As natural polysaccharide biomaterials, chitosan-based hydrogels exhibit the advantages of flexibility, biocompatibility, mechanical tunability, and stimuli sensitivity, and could serve as an excellent interface for bioelectronic sensors. Based on the fabrication approaches, interaction mechanisms, and bioelectronic communication modalities, this review divided chitosan-based hydrogels into four types, including electrode-based hydrogels, conductive materials conjugated hydrogels, ionically conductive hydrogels, and redox-based hydrogels. To introduce the enhanced performance of bioelectronic sensors, as a complementary alternative, the incorporation of nanoparticles and redox species in chitosan-based hydrogels was discussed. In addition, the multifunctional properties of chitosan-based composite hydrogels enable their applications in biomedicine (e.g., smart skin patches, wood healing, disease diagnosis) and food safety (e.g., electrochemical sensing, smart sensing, artificial bioelectronic tongue, fluorescence sensors, surface-enhanced Raman scattering). We believe that this review will shed light on the future development of chitosan-based biosensing hydrogels for micro-implantable devices and human–machine interactions, as well as potential applications in medicine, food, agriculture, and other fields.